Exocytosis in non‐neuronal cells. Issue 6 (2nd May 2016) - Thorn, Peter; Zorec, Robert; Rettig, Jens; Keating, Damien J.
Abstract: Exocytosis is the process by which stored neurotransmitters and hormones are released via the fusion of secretory vesicles with the plasma membrane. It is a dynamic, rapid and spatially restricted process involving multiple steps including vesicle trafficking, tethering, docking, priming and fusion. For many years great steps have been undertaken in our understanding of how exocytosis occurs in different cell types, with significant focus being placed on synaptic release and neurotransmission. However, this process of exocytosis is an essential component of cell signalling throughout the body and underpins a diverse array of essential physiological pathways. Many similarities exist between different cell types with regard to key aspects of the exocytosis pathway, such as the need for Ca 2+ to trigger it or the involvement of members of the N ‐ethyl maleimide‐sensitive fusion protein attachment protein receptor protein families. However, it is also equally clear that non‐neuronal cells have acquired highly specialized mechanisms to control the release of their own unique chemical messengers. This review will focus on several important non‐neuronal cell types and discuss what we know about the mechanisms they use to control exocytosis and how their specialized output is relevant to the physiological role of each individual cell type. These include enteroendocrine cells, pancreatic β cells, astrocytes, lactotrophs and cytotoxic T lymphocytes. Non‐neuronal cells have acquired highly specialized mechanisms to control the release of unique chemical messengers, such as polarised fusion of insulin granules in pancreatic β cells targeted towards the vasculature (top). This review discusses mechanisms used in several important non‐neuronal cell types to control exocytosis, and the relevance of intermediate vesicle fusion pore states (bottom) and their specialized output to the physiological role of each cell type. These include enteroendocrine cells, pancreatic β cells, astrocytes, lactotrophs and cytotoxic T lymphocytes. This article is part of a mini review series on Chromaffin cells (ISCCB Meeting, 2015) . Abstract : Non‐neuronal cells have acquired highly specialized mechanisms to control the release of unique chemical messengers, such as polarised fusion of insulin granules in pancreatic β cells targeted towards the vasculature (top). This review discusses mechanisms used in several important non‐neuronal cell types to control exocytosis, and the relevance of intermediate vesicle fusion pore states (bottom) and their specialized output to the physiological role of each cell type. These include enteroendocrine cells, pancreatic β cells, astrocytes, lactotrophs and cytotoxic T lymphocytes. This article is part of a mini review series on Chromaffin cells (ISCCB Meeting, 2015) .